De-escalation of regional nodal irradiation fields in pT1-2N1 breast cancer patients after breast conserving surgery: retrospective real-world clinical experience - Hong, Ji Hyun; Song, Jin-Ho; Choi, Kyu-Hye; Kim, Shin Woo; Park, Woo-Chan; Lee, Jieun; Lee, Ahwon; Kang, Jun; Choi, Byung-Ock (Frontiers in Oncology, 2025)
PurposeRegional nodal irradiation (RNI) in pN1 patients with one to three positive axillary lymph node breast cancers remains controversial. This study aimed to evaluate the impact of RNI in patients with pT1-2N1 breast cancer who underwent radiotherapy after breast-conserving surgery (BCS), focusing on risk stratification and defining the extent of RNI as axillary lymph node levels I and II.MethodsFemale patients with pT1-2N1 breast cancer after BCS with axillary lymph node dissection or sentinel lymph node biopsy who were treated with radiotherapy between 2009 and 2021 were identified. Radiotherapy included either whole-breast irradiation (WBI) alone or WBI with RNI to axillary levels I and II. Patients were categorized into three risk groups based on pathological T stage, number of positive lymph nodes, and immunohistochemical classification.ResultsA total of 464 patients were analyzed, with a median follow-up of 68.5 months. A total of 212 (45.7%) patients received WBI alone, and 252 (54.3%) received WBI with RNI. Overall, RNI did not significantly improve disease-free survival (DFS) (p = 0.317), locoregional recurrence-free survival (LRRFS) (p = 0.321), distant metastasis-free survival (DMFS) (p = 0.452), or overall survival (OS) (p = 0.721). However, RNI demonstrated a significant benefit in terms of LRRFS (p = 0.014) in the high-risk group. Case–control matched analysis showed robust benefits in DFS (p = 0.020), LRRFS (p = 0.030), and marginal improvement in DMFS (p = 0.066) in the high-risk group. The toxicities were comparable between WBI alone and WBI with RNI.ConclusionsRNI omission may be considered in low-risk patients with pT1 and one positive lymph node. High-risk patients with pT2, two to three lymph nodes, or triple-negative breast cancer may benefit from RNI. De-escalation of the RNI extent might be considered for non-inferior survival outcomes with comparable toxicities.